The Relevance of Fiqh Muamalah Study in the Development of the Digital Economy - Muhammad Ibnu Baihaqie; Mohammad Ridwan; Gama Pratama (Ecobankers : Journal of Economy and Banking, 2026)
The development of the digital economy has brought significant changes to the economic transaction patterns of society, including Muslims. This transformation is marked by the emergence of various innovations such as e-commerce, financial technology (fintech), digital wallets, and blockchain-based systems. This situation demands a reexamination of muamalah jurisprudence (fiqh) to ensure its relevance and applicability. This article aims to analyze the relevance of muamalah jurisprudence in responding to the dynamics of the digital economy, emphasizing the application of fiqh principles and the maqasid (objectives) of sharia. This research uses a literature review method with a conceptual approach, drawing on classical and contemporary sources. The results indicate that muamalah jurisprudence is flexible and adaptive, capable of accommodating developments in the digital economy as long as it does not conflict with sharia principles. Thus, muamalah jurisprudence continues to play a strategic role as a normative and ethical foundation for building a just and welfare-oriented digital economic system